Altered Insula Activity during Visceral Interoception in Weight-Restored Patients with Anorexia Nervosa - Kerr, Kara L (Neuropsychopharmacology, 2016)
Anorexia nervosa (AN) is a devastating psychiatric illness that is associated with significant morbidity and mortality. Aberrant visceral interoceptive processing within the insula has been hypothesized to be an important mechanism in AN's pathophysiology due to the theoretical link between interoception and emotional experience. We therefore utilized functional magnetic resonance imaging (fMRI) to examine whether altered insula functioning underlies visceral interoception in AN. Fifteen females with restricting-type AN and 15 healthy control females underwent fMRI while performing an interoceptive attention task during which they focused on sensations in their heart, stomach, and bladder. Participants also performed an anxious rumination task while in the scanner. AN participants were weight-restored and free of psychotropic medications. Two distinct regions of the insula—anterior insula and dorsal mid-insula—exhibited a significant (p<0.05) interaction between group and interoceptive modality. The post hoc analyses revealed that in the dorsal mid-insula the interaction was driven by group differences during stomach interoception (p=0.002, Bonferroni corrected), whereas in the anterior insula the interaction was driven by group differences during heart interoception (p=0.03, Bonferroni corrected). In addition, individuals with AN displayed increased activation during anxious rumination in the dorsal mid-insula, and activation in this region during stomach interoception was correlated with measures of anxiety and psychopathology. This relationship between altered visceral interoception and clinical symptoms in AN suggests an important mechanism for the disorder. Additional research is needed to examine whether interventions targeting visceral interoception may increase the efficacy of treatments for AN.